Emotional well-being in children and adolescents treated with atomoxetine for attention-deficit/hyperactivity disorder: Findings from a patient, parent and physician perspective using items from the pediatric adverse event rating scale (PAERS) - Dittmann Ralf W; Lehmann Martin; Schacht Alexander; Wehmeier Peter M; Silva Susan G; March John S (BMC, 2008)
Abstract Background The objective of this analysis was to measure changes in items on the Pediatric Adverse Event Rating Scale (PAERS) that relate to emotional well-being of children and adolescents with Attention-Deficit/Hyperactivity Disorder (ADHD) during treatment with atomoxetine for up to 24 weeks from the perspective of the patient, the parent, and the physician. Methods Patients aged 6-17 years with ADHD were treated with atomoxetine (target dose 1.2 mg/kg/day). In the two studies on which this secondary analysis is based the PAERS was used to assess the tolerability of atomoxetine in children and adolescents. This scale has a total of 48 items. The ten items that reflect emotional well-being were selected to measure changes over time from a patient, parent, and physician perspective. Results 421 patients were treated with atomoxetine. 355 patients completed the 8-week treatment period, and 260 patients completed the 24-week treatment period. The ten items that reflect emotional well-being were grouped in five dimensions: depressed mood, self-harm, irritability/agitation, drowsiness, and euphoria. The scores of these dimensions decreased over time, both from a patient as well as from a parent and physician perspective. Only the dimension self-harm was extremely low at baseline and stayed low over time. The mean scores for the ten items depended on the rater perspective. Conclusion The emotional well-being of children and adolescents with ADHD improved in terms of depressed mood, irritability/agitation, drowsiness, and euphoria during treatment with atomoxetine for up to 24 weeks.